Microwave Absorption Analysis of Barium Hexaferite And Iron Sand - Naibaho, Yeni P. S.; Humaidi, Syahrul; Rianna, Martha; Diana, Linda E. (Journal of Applied Geospatial Information, 2024)
The goal of this study is to investigate the properties of barium hexaferrite and iron sand as microwave absorbers. The focus is on understanding how these materials affect microwave absorption and the specific frequency range of waves they produce. The solid reaction method was used in the study. The study's findings indicate that the combination of iron sand with barium hexaferrite material leads to the formation of a homogeneous material with a single phase. X-ray diffraction pattern data confirms the presence of a single-phase material, specifically iron sand and barium hexaferrite, which consists of hematite and barium hexaferrite. The VNA observations reveal that the iron sand and barium hexapherite materials can absorb electromagnetic waves at a radar wave frequency of 11.1 GHz, resulting in a loss of -23.86 dB. Furthermore, the material demonstrates its ability to absorb microwaves. The absorption of microwaves relies on the quantity of particles in the absorbent substance and its microwave-absorbing capacity. To thoroughly assess the absorption properties of various samples, it is essential to not only evaluate their reflection loss but also analyze how well they operate as microwave absorbers.